Civil Society, Health, and Social Exclusion in Bangladesh (Journal of Health, Population and Nutrition, 2009)
Civil society has the potential to have a positive impact on social exclusion and health equity through active monitoring and increased accountability. This paper examines the role of civil society in Bangladesh to understand why this potential has not been realized. Looking at two models of civil society action- participation in decentralized public-sector service provision and academic think-tank data analysis-this analysis examines the barriers to positive civil society input into public policy decision-making. The role of non-governmental organizations, political, cultural and economic factors, and the influence of foreign bilateral and multilateral donors are considered. The paper concludes that, with a few exceptions, civil society in Bangladesh replicates the structural inequalities of society at large. Key words: Civil society; Health equity; Health systems; Participation; Social exclusion; Bangladesh doi: 10.3329/jhpn.v27i4.3400 J Health Popul Nutr 2009 Aug;27(4):536-544